Hubungan antara Postur Kerja dan Keluhan Muskuloskeletal pada Pekerja Kantoran : Literature Review - Ramadhan, Yasmine Aulia; Wardani, Dyah Wulan Sumekar Rengganis; Komala, Ramadhana; Berawi, Khairunnisa (CV. Jasa Sukses Abadi, 2024)
Musculoskeletal disorders (MSDs) are commonly experienced by office workers, particularly those who spend long hours working in front of computers with non-ergonomic postures. Frequent complaints such as pain in the neck, back, arms, and wrists are often caused by unsupported sitting positions or the use of work equipment that does not adhere to ergonomic principles. An evaluation to understand the relationship between work posture and musculoskeletal complaints among office workers is necessary to assess its risk level for MSDs.. One effective method to assess MSD risk is the Rapid Office Strain Assessment (ROSA). This method evaluates three key aspects of the work environment: chair design, monitor position, and the placement of the mouse and keyboard, all of which significantly impact worker comfort and health. The assessment assigns scores to each element to determine the level of risk. Studies reveal that many workers face high risks due to non-ergonomic working postures, which directly contribute to musculoskeletal complaints. Implementing ergonomic principles, such as using chairs that support proper posture, adjusting desk height to match the worker's stature, and optimizing computer device arrangements, is crucial to reducing these risks. Additionally, incorporating breaks for stretching into work schedules is strongly recommended. These measures not only alleviate MSD complaints but also enhance workplace comfort and overall productivity.